Hysteretic Ion Migration and Remanent Field in Metal Halide Perovskites. Issue 19 (19th August 2020) - Liu, Yongtao; Borodinov, Nikolay; Lorenz, Matthias; Ahmadi, Mahshid; Kalinin, Sergei V.; Ievlev, Anton V.; Ovchinnikova, Olga S.
Abstract: The gap in understanding how underlying chemical dynamics impact the functionality of metal halide perovskites (MHPs) leads to the controversy about the origin of many phenomena associated with ion migration in MHPs. In particular, the debate regarding the impact of ion migration on current–voltage ( I – V ) hysteresis of MHPs devices has lasted for many years, where the difficulty lies in directly uncovering the chemical dynamics, as well as identifying and separating the impact of specific ions. In this work, using a newly developed time‐resolved time‐of‐flight secondary ion mass spectrometry CH3 NH3 + and I − migrations in CH3 NH3 PbI3 are directly observed, revealing hysteretic CH3 NH3 + and I − migrations. Additionally, hysteretic CH3 NH3 + migration is illumination‐dependent. Correlating these results with the I – V characterization, this work uncovers that CH3 NH3 + redistribution can induce a remanent field leading to a spontaneous current in the device. It unveils that the CH3 NH3 + migration is responsible for the illumination‐associated I – V hysteresis in MHPs. Hysteretic ion migration has not been uncovered and the contribution of any ions (e.g., CH3 NH3 + ) has not been specified before. Such insightful and detailed information has up to now been missing, which is critical to improving MHPs photovoltaic performance and developing MHPs‐based memristors and synaptic devices. Abstract : Ion migration plays critical roles in the functionalities of metal halide perovskites. Herein, using newly developed time‐resolved time‐of‐flight secondary ion mass spectrometry, hysteretic CH3 NH3 + and I − migrations in CH3 NH3 PbI3 are observed, where CH3 NH3 + migration hysteresis is illumination‐dependent. The ion redistribution in CH3 NH3 PbI3 can lead to a permanent spontaneous current after the application of electric bias.